Transneuronal Circuit Analysis with Pseudorabies Viruses. Issue 1 (1st July 2014) - Card, J. Patrick; Enquist, Lynn W.
Abstract: Our ability to understand the function of the nervous system is dependent upon defining the connections of its constituent neurons. Development of methods to define connections within neural networks has always been a growth industry in the neurosciences. Transneuronal spread of neurotropic viruses currently represents the best means of defining synaptic connections within neural networks. The method exploits the ability of viruses to invade neurons, replicate, and spread through the intimate synaptic connections that enable communication among neurons. Since the method was first introduced in the 1970s, it has benefited from an increased understanding of the virus life cycle, the function of viral genome, and the ability to manipulate the viral genome in support of directional spread of virus and the expression of transgenes. In this unit, we review these advances in viral tracing technology and the way in which they may be applied for functional dissection of neural networks. Curr. Protoc. Neurosci . 68:1.5.1‐1.5.39. © 2014 by John Wiley & Sons, Inc.